The names of friendship: Questions for the imagination of other relational horizons - Braga, Ana Luiza; Botelho, Catarina (Re-visiones, 2024)
In face of advancing precariousness brought forth by neoliberal policies and the resurgence of conservative movements, we discuss how friendships could be a space of reinvention of social relations and resistance, constituting dissident affective bonds and support networks. We address, through a micropolitical and affirmative approach, the transformative potential of making kin outside biological and sexual relations, as well as of inventing fugitive forms of instituting such ties, particularly amongst queer-feminist subjects. By activating the speculative and political imagination, we inquire the ways in which we can visibilize, perform and materialize these relationships, opening up distinct social and subjective spaces that could allow us alternative presents and futures together beyond heteronormative structures.
Keywords: Friendship; kinship; interdependence; precarization; care; queer-feminist politics; modes of existence; micropolitics; political imagination; speculative feminisms